Political Socialization and Collective Memory in Algeria: The Senior Generation (1945 - 1960) and the Legacy of Independence in the Context of the Hirak. - Akpinar, Salih (Université d'Ottawa | University of Ottawa, 2025)
This thesis examines the 2019/2020 Hirak protests in Algeria to explore why some retired individuals engage in social movements while others do not. The Hirak protests provide a compelling case study for analyzing participation and non-participation within the context of an authoritarian regime. Algeria, which gained independence in 1962, still has individuals who lived through the war of liberation from 1954 to 1962, offering a unique perspective on contemporary collective action and social movement analysis. The Hirak protests emerged as a response to President Bouteflika’s proposed fifth term, escalating into widespread regional and national demonstrations and continuous street occupations across the country for over a year. These protests marked an unprecedented scale and diversity of mobilization, involving people of all ages and backgrounds, including men, women, workers, and the unemployed. However, scholarly research has largely overlooked the involvement of the elderly, prompting essential questions about the social and political factors influencing participation and non-participation among older generations. This research utilizes semi-structured interviews with 35 retired individuals from Tizi-Ouzou, Algiers, and Mostaganem to analyze the social and political dynamics distinguishing activists from non-activists. By integrating the concepts of generation and habitus as structural frameworks for actor networks, the study suggests that social class can both inhibit and enable participation. It investigates whether the attitudes of the elderly, when viewed collectively, point to a discernible generational identity. The research delves into how elderly activist networks are formed and maintained, focusing on their socialization processes and class affiliations. Additionally, it explores the social networks of non-participants, assessing how these structures contribute to the emergence and persistence of non-participation at the individual level. The main findings of the research suggest that it is indeed possible to assert the existence of a war generation in Algeria. The Algerian War of Independence is indeed a foundational event for the studied generation born during the 1950s. This war and its symbols emerge as the most significant political schism for elderly Algerians, if not for all. Secondary socialization has a greater impact on the political activism of elderly individuals than primary socialization. Algerian activists tend to engage politically predominantly with peers of their own generation. Not being politicized, not being recruited at a young age, not knowing activists, and the lack of a solid background of participation in protest events and social movements constitute strong barriers to elderly activism. Moreover, being employed by the government, affiliating with civil organizations that lack autonomy from governmental control, and having family members in government employment diminish the probability of sustaining activism as a lifelong endeavor. The preservation of financial and intellectual sovereignty, especially found within a marginalized elite, is the key driver of an individual’s lifelong political commitment.
Keywords: Social Movements; Algerian Hirak; Elderly Activism; Authoritarianism